Analisis Penetapan Surat Dakwaan Terhadap Suatu Tindak Pidana - Fitriani, Rahma Eka; Asshofa, M. Muhibin; Humaeroh, Nisbati Sandiah (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2022)
Abstract:An indictment in court is comparable to a diamond that the public prosecutor must zealously keep and defend. The indictment serves as both a foundation for the judge to conduct an examination during court proceedings and a basis for the judges’ consideration when they deliberate to reach a conclusion. While simultaneously restricting the scope of the examination, the indictment plays a crucial role in the Court’s consideration of criminal matters. So that the ability, skill and foresight of the Public Prosecutor are required in preparing the indictment so that the articles of the Criminal Code which will later be imposed on the defendant are right on target, so that the accused can sentenced according to the crime committed. Errors in drafting the indictment will result in a case that can be acquitted or released from all lawsuits or null and void, and will cause various obstacles in efforts to prove the indictment. This time the author examines the material regarding the indictment using the literary method, where in the drafting process it is based on literature, both with books, articles, journals, and reports on the results of previous research. Keyword: Indictment, Court, criminal.